SPECIAL EDUCATION FROM AN ISLAMIC PERSPECTIVE - Sumarna, Elan; Jaedi, M; Nurjaman, Asep Rudi; Jenuri, Jenuri; Hidayat, Tatang (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Children with Special Needs is the term used to describe children who have developmental disorders. These disorders can arise due to internal factors within the child's own development or external factors. Because of these limitations, people, especially in developing countries, generally perceive them as children who have lost their right to education and empowerment. Purpose: This article aims to present the results of research related to the right to education for Children with Special Needs from an Islamic education perspective. Method: This research uses library research methods by attempting to analyze the collected data (content analysis), both from the Qur'an and the Hadith, and of course from sources published in scientific journals about their right to education. The general view of children with special needs is that they are exempt from legal obligations and empowerment. Therefore, the role of Islamic education is very much needed to change the negative paradigm of society towards them. Conclusion: Children with special needs in Islam, with all their limitations, are still regarded as Muslims who do not lose their rights and obligations and are not stripped of their title as caliphs of Allah SWT on this earth.